2009
DOI: 10.3171/2009.2.jns08284
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of basioccipital hypoplasia in Chiari malformation Type I: comparative morphometric study of the posterior cranial fossa

Abstract: Data in this study support the idea that occipital hypoplasia is the main cause of overcrowding within the PCF. Basioccipital shortness is a cardinal feature of the resultant shallow PCF and could proceed from a congenital disorder of the cephalic mesoderm of the parachordal plate or occur later in the infancy because of premature stenosis of the sphenooccipital synchondrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
68
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 31 publications
(96 reference statements)
13
68
3
2
Order By: Relevance
“…PCF volumes measured by use of the automated method and with manual delineation were found to be similar, 196.2 ± ± 8.7 vs. 196.9 ± 11.0 cm 3 , respectively. The mean PCF volumes previously reported in CT and magnetic resonance-based measurements of 186 cm 3 by Nishikawa et al [7], 174 ± 25 cm 3 by Noudel et al [8] and 166 ± 8 cm 3 by Milhorat et al [5] and 165.57 ± ± 19.37 cm 3 by Vurdem et al [11]. As for our finding, PCF volume was 100.91 cm 3 .…”
Section: Case Reportsupporting
confidence: 75%
See 1 more Smart Citation
“…PCF volumes measured by use of the automated method and with manual delineation were found to be similar, 196.2 ± ± 8.7 vs. 196.9 ± 11.0 cm 3 , respectively. The mean PCF volumes previously reported in CT and magnetic resonance-based measurements of 186 cm 3 by Nishikawa et al [7], 174 ± 25 cm 3 by Noudel et al [8] and 166 ± 8 cm 3 by Milhorat et al [5] and 165.57 ± ± 19.37 cm 3 by Vurdem et al [11]. As for our finding, PCF volume was 100.91 cm 3 .…”
Section: Case Reportsupporting
confidence: 75%
“…Recently, morphometric studies have clearly shown significantly smaller volume or underdeveloped bony parts of the PCF in adults [1][2][3]5]. A significant smaller basiocciput in CMI group was demonstrated by Noudel et al [8], but no significant difference was found in the length of the supraocciput and FM. No significant difference in the length of the clivus, basiocciput and spheniocciput between the CMI and the control group was reported by Nishikawa et al [7].…”
Section: Case Reportmentioning
confidence: 89%
“…1,8,10,12,28 It is likely that patients with CM-I have a reduced posterior fossa volume, which results in crowding at the foramen magnum. 6,21,25,27 Although cerebellar tonsil position is a convenient marker for crowding at the foramen magnum, the correlation is not exact. 26 In some cases, patients with < 5 mm of descent can have a clinical presentation of Chiari syndrome and even syringomyelia caused by crowding at the foramen magnum.…”
Section: Discussionmentioning
confidence: 99%
“…134 Children with CM often have a smaller than normal posterior fossa volume, resulting in crowding of the posterior fossa and foramen magnum contents. [142][143][144] This crowding at the foramen magnum may be appreciated on sagittal MRI by the typical "pegshaped" appearance of the cerebellar tonsils. Because "crowding" is difficult to quantify or objectively determine, the diagnosis of CM on imaging is usually made by a determination of cerebellar tonsil position on MRI.…”
Section: Chiari and Syringomyeliamentioning
confidence: 99%